Genetic parameters for birth and weaning weight in a herd of Mediterranean buffaloes under tropical conditions - Iván A. Cárdenas; Miguel A. Chacón (Revista Científica)
The objectives of the present study were to estimate variance components and genetic parameters for birth weight (BW) and weaning weight (WW). The data comes from Mediterranean buffalo calves born during the period from August 2003 to December 2021 on the Livestock Farm “Hacienda Caño Negro”, located near the population of Santa Barbara del Zulia, Venezuela. A total of 2225 records collected for BW and WW were included in the analysis. Variance components and genetic parameters were estimated by REML using the MTDFREML program, applying a bivariate animal model that includes direct, maternal, and permanent maternal effects. The population average BW of Buffalo calves was 42.7±0.1 kg, whereas for males, 43.9±0.2 and for females, 41.7±0.2 kg. The population average for WW was 174.5+0.9 kg. According to sex, the WW parameters were 178.5±1.3 kg and 170.5±1.1 kg in males and females, respectively. The direct heritability estimates were 0.03 and 0.23 for BW and WW, respectively, whereas maternal heritability values were 0.78 for BW and 0.24 for WW. The estimated total heritability for both characters was 0.23 (BW) and 0.32 (WW). The genetic correlation  between BW and WW was 0.57, while the maternal genetic correlation for BW and WW was 0.01. The results indicated moderate total heritability value for BW and WW; further analysis is needed to estimate the genetic parameters, perhaps including other breed herds.